Protection of bradykinin on neonatal rat myocytes subjected to anoxia/reoxygenation injury - Tang Zi-lue; Wu Wen-jian; Fan Yun-xiang; Deng Han-wu; Chen Xiu (Acta Pharmacologica Sinica, 2016)
This study was to investigate the effects of bradykinin (BK) on myocyte cultures. The effects of BK against lipid peroxidation and oxygen free radicals were estimated on an anoxia/reoxygenation injured model. A salicylate hydroxylation product dihydroxybenzoic acids (DHBA) was detected using HPLC with electrochemical detection, a sensitive device for assaying the hydroxyl free radical. BK (10 nmol.L-1) reduced thiobarbituric acid reactive substances (TBARS, from 1.94 +/- s 0.28 to 0.25 +/- 0.03 nmol/10(6) cells, n = 5, P < 0.01), lactate dehydrogenase (LDH) release (1.28 +/- 0.23 to 0.63 +/- 0.12 u.ml-1, n = 8, P < 0.01) and DHBA (60 +/- 5 to 44 +/- 12 nmol.L-1, n = 6, P < 0.01). These improvements were nullified by pretreatment with K86/4321 (1 mumol.L-1), a kind of BK receptor antagonist. Indometacin (Ind, 1 mumol.L-1) had a synergic action with BK to decrease the LDH release, but Ind (30 mumol.L-1) attenuated the protection of BK, while both LDH and TBARS were increased. The mechanism for protection of BK was ascribable to the activation of BK receptor, the inhibition of lipid peroxidation, and the decreased hydroxyl free radical formation.